Loading in 5 sec....

2.5 Apply the Remainder and Factor Theorems p. 120PowerPoint Presentation

2.5 Apply the Remainder and Factor Theorems p. 120

- 109 Views
- Uploaded on
- Presentation posted in: General

2.5 Apply the Remainder and Factor Theorems p. 120

Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.

- - - - - - - - - - - - - - - - - - - - - - - - - - E N D - - - - - - - - - - - - - - - - - - - - - - - - - -

2.5 Apply the Remainder and Factor Theorems p. 120

How do you divide polynomials?

What is the remainder theorem?

What is the difference between synthetic substitution and synthetic division?

What is the factor theorem?

When you divide a Polynomial f(x) by a divisor d(x), you get a quotient polynomial q(x) with a remainder r(x) written:f(x) = q(x) + r(x)d(x) d(x)

- You write the division problem in the same format you would use for numbers. If a term is missing in standard form …fill it in with a 0 coefficient.
- Example:
- 2x4 + 3x3 + 5x – 1 =
- x2 – 2x + 2

2x2

2x4 = 2x2

x2

2x2

+7x

+10

-( )

2x4

-4x3

+4x2

7x3

- 4x2

+5x

-( )

7x3 - 14x2 +14x

10x2 - 9x

-1

7x3 = 7x

x2

-( )

10x2 - 20x +20

11x - 21

remainder

- 2x2 + 7x + 10 + 11x – 21 x2 – 2x + 2
- Quotient + Remainder over divisor

- y4 + 2y2 – y + 5 =y2 – y + 1
- Answer: y2 + y + 2 + 3 y2 – y + 1

2. (x3–x2 + 4x – 10) (x + 2)

SOLUTION

Write polynomial division in the same format you use when dividing numbers. Include a “0” as the coefficient of x2 in the dividend. At each stage, divide the term with the highest power in what is left of the dividend by the first term of the divisor. This gives the next term of the quotient.

quotient

)

x + 2

x3 – x2 + 4x – 10

x3 + 2x2

– 3x2– 6x

10x + 20

remainder

x2 – 3x + 10

Multiply divisor byx3/x = x2.

Subtract. Bring down next term.

–3x2 + 4x

Multiply divisor by –3x2/x= –3x.

Subtract. Bring down next term.

10x – 1

Multiply divisor by10x/x = 10.

– 30

ANSWER

x3 – x2 +4x – 10

– 30

= (x2 – 3x +10)+

x + 2

x + 2

OR…

- (x3–x2 + 4x – 10) (x + 2)
- Set x + 2 = 0.
- Solve for xx = −2
- Use − 2 as the divisor for synthetic division which is the same as synthetic substitution.
- Synthetic division can be used to divide any polynomial by a divisor of the form “x −k”

- If a polynomial f(x) is divisible by (x – k), then the remainder is r = f(k).
- Now you will use synthetic division (like synthetic substitution)
- f(x)= 3x3 – 2x2 + 2x – 5
- Divide by x - 2

– 21 −1 4 −10

– 2 6 – 20

1 – 3 10 – 30

ANSWER

SOLUTION

F(x) = x3–x2 + 4x – 10 (x + 2)

- Long division results in ?......
- 3x2 + 4x + 10 + 15 x – 2
- Synthetic Division:
- f(2) = 3-22-52

6

8

20

3

4

10

15

Which gives you:

+ 15

x-2

3x2

+ 10

+ 4x

- Divide x3 + 2x2 – 6x -9 by (a) x-2 (b) x+3
- (a) x-2
- 12-6-9 2

8

4

2

1

4

2

-5

Which is x2 + 4x + 2 + -5 x-2

- (b) x+3
- 12-6-9 -3

3

9

-3

1

-1

-3

0

x2 – x - 3

- A polynomial f(x) has factor x-k if f(k)=0
- note that k is a ZERO of the function because f(k)=0

- Factor f(x) = 2x3 + 11x2 + 18x + 9
- Given f(-3)=0
- Since f(-3)=0
- x-(-3) or x+3 is a factor
- So use synthetic division to find the others!!

- 211189
- -3

-15

-9

-6

2

5

3

0

So…. 2x3 + 11x2 + 18x + 9 factors to:

(x + 3)(2x2 + 5x + 3)

Now keep factoring-- gives you:

(x+3)(2x+3)(x+1)

4 1 – 6 512

4– 8 –12

1 – 2 – 3 0

Factor the polynomial completely given that x –4 is a factor.

f (x) = x3– 6x2 + 5x + 12

SOLUTION

Because x – 4 is a factor of f (x), you know that f (4)= 0. Use synthetic division to find the other factors.

Use the result to write f (x) as a product of two factors and then factor completely.

f (x) = x3– 6x2+ 5x + 12

Write original polynomial.

= (x – 4)(x2– 2x – 3)

Write as a product of two

factors.

= (x – 4)(x –3)(x + 1)

Factor trinomial.

- Factor f(x)= 3x3 + 13x2 + 2x -8
- given f(-4)=0
- (x + 1)(3x – 2)(x + 4)

- f(x) = x3 – 2x2 – 9x +18.
- One zero of f(x) is x=2
- Find the others!
- Use synthetic div. to reduce the degree of the polynomial function and factor completely.
- (x-2)(x2-9) = (x-2)(x+3)(x-3)
- Therefore, the zeros are x=2,3,-3!!!

- f(x) = x3 + 6x2 + 3x -10
- X=-5 is one zero, find the others!
- The zeros are x=2,-1,-5
- Because the factors are (x-2)(x+1)(x+5)

- How do you divide polynomials?
By long division

- What is the remainder theorem?
If a polynomial f(x) is divisible by (x – k), then the remainder is r = f(k).

- What is the difference between synthetic substitution and synthetic division?
It is the same thing

- What is the factor theorem?
If there is no remainder, it is a factor.

Page 124, 7, 9, 11-15 odd, 21-23 odd, 29-33 odd, 35- 37 all